AIRBORNE PARTICULATE MATTER IN ASTANA, KAZAKHSTAN: POTENTIALLY TOXIC ELEMENTS, LUNG BIOACCESSIBILITY, AND RISK ASSESSMENT - Agibayeva, Akmaral (Nazarbayev University, School of Engineering and Digital Sciences, 2024)
The degradation of air quality remains one of the most critical environmental concerns. Exposure to airborne pollutants is extensively associated with various health conditions, including respiratory and cardiovascular diseases, and premature death. The health risks of air pollution have been linked to particulate matter (PM) and its constituents. Potentially Toxic Elements (PTEs) in atmospheric PM are a critical factor contributing to its toxicity. This doctoral thesis addresses multiple aspects of air quality in Astana, Kazakhstan, offering a holistic understanding of the local air pollution situation through (1) analysis of PM and gaseous pollutant concentration; (2) proposing a modification to the toxicity assessment of PM-bound PTEs via in vitro lung bioaccessibility; (3) the assessment of health risk due to inhalation exposure to PM using bioaccessible concentration of PTEs; (4) morphological characterization of PM; (5) source identification; (6) studying precipitation chemistry and its role in air pollution; and (7) assessment of the public knowledge, perception and attitude towards local air quality in Astana. The methodological framework involved primary data analysis (342 PM samples collected in Astana, Kazakhstan from 2021 to 2023) and air pollution data obtained from monitoring stations located in the city (S1-S6) in 2018-2020. Annual and 24-hour mean concentrations of PM2.5, PM2.5-10, and gaseous pollutants (SO2, CO, NO2, NO, and HF) were, in general, higher than established national and international (World Health Organization (WHO)) maximum permissible levels (e.g., for PM2.5 annual mean of 29.7 μg/m3 in 2018-2019; and 24-hour mean of 28.7 μg/m3 (maximum: 534 μg/m3) for PM2.5 and 226 μg/m3 (maximum: 1,564 μg/m3) for PM2.5-10, respectively, in 2021-2023). To simulate real-life inhalation exposure to PM-bound PTEs, the assessment was conducted through optimization of in vitro lung bioaccessibility testing in simulated lung fluids (SLF) (i.e., modified Gamble’s solution (GS) and Artificial Lysosomal Fluid (ALF)). For a modification of commonly established methodology, a large set of PTEs (Cd, Co, Cr, Cu, Mn, Ni, Pb, Sb, V, and Zn) has been investigated using seven distinct formulations of GS, one ALF on two reference materials (SRM 2691 and BGS 102).
Keywords: particulate matter; inhalation bioaccessibility; risk assessment; type of access: embargo